2015
DOI: 10.1614/ws-d-14-00020.1
|View full text |Cite
|
Sign up to set email alerts
|

Aminocyclopyrachlor Absorption and Translocation in Three Aquatic Weeds

Abstract: Studies were conducted to evaluate 14C-aminocyclopyrachlor absorption and translocation in alligatorweed, waterhyacinth, and waterlettuce. Alligatorweed plants were treated at the seven-node stage, waterhyacinth was treated at the five-leaf stage, and waterlettuce was treated at the eight-leaf stage. All plants were pretreated with nonlabeled aminocyclopyrachlor at 0.14 kg ai ha−1 with 1% (v/v) methylated seed oil (MSO). 14C-aminocyclopyrachlor was then applied to a protected leaf, and plants were harvested at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For instance, differential activity of canola to picloram and clopyralid was not due to differences in translocation, absorption, or metabolism (Hall and Vanden Born 1988). Similarly, Israel et al (2015) reported that absorption and translocation of AMCP were similar among species such as water lettuce (Pistia stratiotes L.), alligatorweed [Alternanthera philoxeroides (Mart.) Griseb.…”
mentioning
confidence: 97%
“…For instance, differential activity of canola to picloram and clopyralid was not due to differences in translocation, absorption, or metabolism (Hall and Vanden Born 1988). Similarly, Israel et al (2015) reported that absorption and translocation of AMCP were similar among species such as water lettuce (Pistia stratiotes L.), alligatorweed [Alternanthera philoxeroides (Mart.) Griseb.…”
mentioning
confidence: 97%
“…Griseb., Eichhornia crassipes (Mart.) Solms, Pistia stratiotes L. (Israel et al ., ), Lolium arundinaceum (Schreb.) Darbysh.…”
Section: Introductionmentioning
confidence: 99%